On Randers Change of a Generalized Exponential Metric - Mishra, Meera; Pandey, R. K. (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2024)
In this paper, we study the properties of a special (α, β)-metric e^(k1β/α)+βe^(k2*β/α), the Randers change of the generalized exponential metric. We find the necessary and sufficient condition for this metric to be locally projectively flat and we also prove the conditions for this metric to be of the Berwald and Douglas type.Keywords: Berwald space; Douglas space; Finsler space; -metric; projectively flat. AbstrakPada artikel ini akan dipelajari sifat-sifat khusus dari (α, β) -metric e^(k1β/α)+βe^(k2*β/α), perubahan Randers dari metrik eksponensial umum. Kami menemukan syarat perlu dan cukup agar metrik ini menjadi datar secara lokal dan kami juga membuktikan syarat agar metrik ini bertipe Berwald dan Douglas.Kata Kunci: ruang Berwald; ruang Douglas; ruang Finsler; -metric; projectively flat. 2020MSC: 53B20.